A Scandinavian Veteran Policy? A Comparative Study of Norwegian, Swedish and Danish Veteran Policies Since 2000 - Vilde Opdan Yttereng (Scandinavian Journal of Military Studies, 2023)
Literature on veteran policies has concentrated on empirical studies of national policies or on factors that shape those policies. There has been little comparative exploration of these matters, particularly in the context of social democratic welfare regimes. This article, based on official documents and interviews, contributes to this literature by studying Scandinavian veteran policies in a comparative light. Between May 2009 and October 2010, Norway, Sweden and Denmark all introduced national veteran policies detailing the care for and recognition of personnel from international operations. The article compares these policies by firstly addressing central similarities and differences and secondly examining factors that explain these. Overall, the veteran policies are found to be strikingly similar, to such an extent that they can essentially be regarded as a Scandinavian veteran policy. The findings support previous research that has highlighted both military developments and social and political factors as shaping veteran policies and add a new factor: international inspiration.